2019
DOI: 10.1109/access.2019.2916168
|View full text |Cite
|
Sign up to set email alerts
|

A New Solar Radiation Model for a Power System Reliability Study

Abstract: The dwindling number of conventional power resources and its environmental impact has motivated a transition to renewable energy sources, such as solar power. Evaluating the reliability of solar power integration into power networks can help decision makers gauge the feasibility of their solar power projects. However, the stochastic and non-stationary nature of solar radiation is difficult to be modeled and can even hinder an accurate evaluation of reliability. A good solar model for accurately assessing solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 25 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Firstly, modelling the failure rates of the PV system requires solar radiation, temperature and humidity data, which are all obtained from the State University of New York Project [33]. The data obtained from two locations, namely, Aceh, Indonesia ( [34] and simulated for 10,000 years. The hourly average of the solar radiation data is obtained from this model and grouped in accordance with the respective months.…”
Section: B Pv System Failure Rate Modelmentioning
confidence: 99%
“…Firstly, modelling the failure rates of the PV system requires solar radiation, temperature and humidity data, which are all obtained from the State University of New York Project [33]. The data obtained from two locations, namely, Aceh, Indonesia ( [34] and simulated for 10,000 years. The hourly average of the solar radiation data is obtained from this model and grouped in accordance with the respective months.…”
Section: B Pv System Failure Rate Modelmentioning
confidence: 99%
“…If an OTEC system with h states is added to the composite system, the number of contingencies would be optimize the cost function, the problem constraints (including the power balance equation must be established, the generated power of generation units must be within the permissible range, the interrupted load must be less than the maximum load and the transmitted power of the transmission lines must be less than nominal capacity) must be satisfied. Based on the contingency analysis, adequacy studies of composite power system containing OTEC systems are performed and reliability indices such as the probability of lost load (QS), LOLE and EENS associated to each load point can be determined using of Relations (24), (25) and (26), respectively. Where, Pi is the probability of state i, Bi is a binary number with two values of 0 and 1 that 1 represents the state results in the load curtailment of understudied bus, n is the number of all states and Li is the value of lost load of understudied load point associated to the state i.…”
Section: The Effect Of Transmission System On the Adequacy Studiesmentioning
confidence: 99%
“…In [25], reliability assessment of distribution network containing renewable resources and parking lots using of the non-sequential Monte Carlo simulation approach is performed and it is concluded that parking lots can improve the reliability of renewable-based distribution networks. In [26], a new robust and easy to use model is developed for simulation solar radiation that can be used for reliability assessment of power systems containing solar generation systems. In [27], a new approach is proposed to evaluate the reliability of wind farms considering the correlation between wind speed and wind turbine reliability.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the ARMA model is used in this paper. As for the modelling of the solar radiation, it has been shown that the proposed model in our previously published paper (see section II.B) [51] is more robust than existing models and it is also used in this paper.…”
Section: A Reliability Test Systemmentioning
confidence: 99%